Analysis of Legal Certainty in Determining the Position, Duties, and Responsibilities of Temporary Notary Officials - Kurniawan, Steven; Dewi, Amelia Sri Kusuma; Wisnuwardhani, Diah Aju (International Journal of Business, Law, and Education, 2023)
The position of a Notary is a crucial part of the Indonesian state that adheres to the principles of a legal state. The Notary is the only public official authorized to create authentic deeds. An authentic deed is a document whose form is determined by the law or is created by or in the presence of a public official authorized for that purpose. This means that an authentic deed has a form stipulated by the law and is created by a public official designated by the law. In the course of performing their duties, notaries may sometimes be unable to fulfill their responsibilities due to reasons such as leave, illness, temporary impediment, or death. Therefore, to continue providing services and being accountable to the public, the position of Temporary Notary Official is established. The procedure for a Temporary Notary Official to perform the duties of a temporarily dismissed notary is explained in Article 80 of the UUJN: "(1) While the Notary is temporarily dismissed from his position, the Central Supervisory Board proposes a Temporary Notary Official to the Minister. (2) The Minister appoints a Notary who will receive the Notary Protocol from the temporarily dismissed Notary." Referring to Article 80 of the UUJN, it can be interpreted that if a notary is temporarily dismissed, the Regional Supervisory Board proposes a Temporary Notary Official to carry out the duties of the temporarily dismissed notary. However, with the development of the law, in 2014, Law Number 30 of 2014 or the UUJN Amendment was enacted, amending the previous UUJN which stated, "Temporary Notary Official is a person who temporarily serves as a Notary to carry out the duties of a Notary who has died." This change was made to ensure legal certainty, order, and protection and also because the UUJN was no longer in line with legal developments and the needs of society. However, the change in the definition was not accompanied by a change in Article 80 of the UUJN, where the Central Supervisory Board proposes a Temporary Notary Official while the Notary is temporarily dismissed. This leads to inconsistency in the law, as in the UUJN Amendment, the Temporary Notary Official is specifically designated to perform the duties of a deceased notary, but the regulation in Article 80 of the UUJN, where the Central Supervisory Board proposes a Temporary Notary Official while the Notary is temporarily dismissed from his position, remains unchanged